GAYA KEPEMIMPINAN WALIKOTA METRO PERIODE 2005 – 2015 - Eko Budi Sulistio; Ita Prihantika; Meiliyana Meiliyana (Wacana Publik, 2018)
This paper aims to identify the leadership style of Metro Mayor 2005-2015, Lukman Hakim. By using a descriptive qualitative approach, it was concluded that during the two periods of being Metro Mayor the leadership style used by Lukman Hakim was a democratic style. With a democratic style, Lukman Hakim's leadership can be considered quite adaptive to the dynamics of the demands of the development of government in Metro City. This is manifested in activities such as APBD surgery, one-stop service or fit and proper tests for officials of government bureaucracy in Metro City in order to realize the demands of the dynamics of democratic governance and clean governance. One result of bureaucratic reform done by Lukman Hakim as Mayor of Metro was the increase in the Public Service Index in 2012 due to the improved performance of the bureaucracy in providing services to the community. Keywords: leadership style, democratic model